Relationship between physical activity level and life satisfaction in young and middle-aged adults and older adults - Magno Giam Honda; Daniele Dias de Melo; Talita Cezareti da Silva; Cleidson Colares Batista; Aline Diniz Gehren; José Roberto Andrade do Nascimento Júnior; Daniel Vicentini de Oliveira (Journal of Physical Education (Maringá), 2025)
This study examined the relationship between physical activity level and life satisfaction among young adults, middle-aged adults, and older adults. Conducted online between June and August 2024, the study included 182 participants aged 18 and older residing in various regions of Brazil. The International Physical Activity Questionnaire and the Life Satisfaction Scale were used. Data analysis was performed using the Kruskal-Wallis test and Spearman correlation, with a significance level of p < 0.05. Results showed that 44.0% of participants were irregularly active, 42.9% were active, and 13.1% were very active. Significant differences were found among age groups in weekly moderate physical activity time and sitting time during weekdays and weekends. Participants aged 30 to 45 reported less moderate activity time, while younger participants (18 to 29 years) had more sitting time. A positive correlation was observed between life satisfaction and moderate-to-vigorous physical activity time and a negative correlation with sedentary behavior, although all correlations were weak. Physical activity was associated with higher life satisfaction, particularly among individuals with moderate to vigorous activity levels, highlighting the importance of promoting physical activity across all age groups to enhance quality of life.